2020
DOI: 10.1002/ijc.33430
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers as triage test for the early identification of cervical lesions in a Chinese population

Abstract: Objective strategies are required in cervical cancer screening. We have identified several DNA methylation markers with high sensitivity and specificity to detect cervical intraepithelial neoplasia 2 or worse (CIN2+) in Dutch women. Our study aims to analyze the diagnostic characteristics of these markers in a Chinese cohort. A total of 246 liquid‐based cytology samples were included, of which 205 women underwent colposcopy due to an abnormal cytology result (atypical squamous cells of undetermined significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
(157 reference statements)
1
19
0
Order By: Relevance
“…In China, plenty of studies have been conducted in the recent years to explore the usage of methylation of human genes (including FAM19A4/EPB41L3/JAM3/MGMT/C13ORF18/ANKRD18CP/ C13ORF18/EPB41L3/JAM3/SOX1/ZSCAN1) in the field of cervical cancer screening, but all those studies were conducted in the clinic settings with relatively small sample size (ranging from 124 to 588). [19][20][21][22][23] Only one study indicated methylation test played a limited role, 21 the other studies showed that the methylation alone or in combination with HPV16/18 could be used as the primary screening testing or triage method for hrHPV positive women. The study with the largest sample size conducted by Gu et al supported that the S5 methylation panel at 2.85 cutoff was superior to HPV16/18 genotyping and cytology for histology HSIL+ (highgrade squamous intraepithelial lesion or worse) detection.…”
Section: Discussionmentioning
confidence: 99%
“…In China, plenty of studies have been conducted in the recent years to explore the usage of methylation of human genes (including FAM19A4/EPB41L3/JAM3/MGMT/C13ORF18/ANKRD18CP/ C13ORF18/EPB41L3/JAM3/SOX1/ZSCAN1) in the field of cervical cancer screening, but all those studies were conducted in the clinic settings with relatively small sample size (ranging from 124 to 588). [19][20][21][22][23] Only one study indicated methylation test played a limited role, 21 the other studies showed that the methylation alone or in combination with HPV16/18 could be used as the primary screening testing or triage method for hrHPV positive women. The study with the largest sample size conducted by Gu et al supported that the S5 methylation panel at 2.85 cutoff was superior to HPV16/18 genotyping and cytology for histology HSIL+ (highgrade squamous intraepithelial lesion or worse) detection.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the full text of the remaining 10 articles was carefully examined, and 4 uncontrolled studies were excluded due to the inability to extract data. Finally, the analysis included a total of six articles [13,[17][18][19][20][21].…”
Section: Process and Results Of Literature Searchmentioning
confidence: 99%
“…JAM3, an adhesion and migration regulatory element, is considered a novel tumor suppressor gene for epigenetic reduction in colorectal cancers [26]. JAM3 is related to the 9 Disease Markers proliferation of cancer cells [27]. Knockdown of JAM3 inhibited the migration of renal cancer cells and promoted the apoptosis of renal cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%